The influence of modified sodium montmorillonite as filler on the performance of glass polyalkenoate cement - Md Nasir, Nur’Izzah; Zainuddin, Norhazlin; Wan Yunus, Wan Md. Zin; Matori, Khamirul Amin (Malaysian Society of Analytical Sciences, 2014)
Modification of sodium montmorillonite (Na-MMT) to aluminium montmorillonite (Al-MMT) and octadecylamine montmorillonite (ODA-MMT) was done by ion exchange process. These MMTs were added as filler to glass polyalkenoate cement(GPC) formulation. The compressive strength and setting reaction of the GPCs were studied. Aluminosilicate glass powder with polyacrylic acid, water and MMT were mixed together with weight ratio of 5:1:1:(1.5wt% powder). The setting reaction was studied from FTIR by monitoring the conversion of COOH in polyacrylic acid to crosslink with metal ions from the glass to form COO-M+ at different aging time. The addition of Al-MMT slightly sped up the setting reaction of GPCs as early as 3 minutes and recorded significant increment in compressive strength at early aging time. While GPC+ODA-MMT only showed increment in compressive strength at early aging time. However, GPC+Na-MMT had shown the slowest performance in GPCs setting reaction and lowest value of the compressive strength. Although the compressive strength for these GPCs was different at early aging time, all cements recorded almost similar compressive strength at day 28. The study highlighted the potential of modified Na-MMT as filler to enhance the performance of GPCs as posterior filling material.